EFEKTIVITAS MODEL PEMBELAJARAN SAVI (SOMATIC, AUDITORY, VISUALIZATION, INTELLECTUALLY) BERBASIS MEDIA FLASHCARD TERHADAP MINAT BELAJAR IPS SISWA KELAS V SDN 137 PALEMBANG - Irma Wulandari; Eni Heldayani; Ali Fakhrudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
This research is motivated by the low interest in learning of fifth grade students at SDN 137 Palembang on social studies material in learning Theme 1 Sub-theme 2. The purpose of the research is to find out (1) the application of the SAVI learning model (Somatic, Auditory, Visualization, Intellectually) based on flashcard media in social studies learning. . class V SDN 137 Palembang, (2) the effectiveness of the flashcard-based SAVI (Somatic, Auditory, Visualization, Intellectually) learning model. This study used a quasi-experimental method with a pretest-posttest non-equivalent control group design. Total sampling is used for sampling. In this study, there were two classes with 42 students, namely class V A as the experimental class and class V B as the control class. Data analysis used t-test using SPSS 25. With a significance value of 5% or 0.05, the tcount was 6.062 so that the ttable was 2.021 and the significant value (2-tailed) = 0.000 <0.05. Thus it can be said that tcount > ttable, then ho is rejected. This shows that there is a difference in learning interest between the experimental class and the control class.